Resolving relaxometry and diffusion properties within the same voxel in the presence of crossing fibres by combining inversion recovery and diffusion‐weighted acquisitions. Issue 1 (2nd March 2015) - De Santis, Silvia; Barazany, Daniel; Jones, Derek K.; Assaf, Yaniv
Abstract : Purpose: A comprehensive image‐based characterization of white matter should include the ability to quantify myelin and axonal attributes irrespective of the complexity of fibre organization within the voxel. While progress has been made with diffusion MRI‐based approaches to measure axonal morphology, to date available myelin metrics simply assign a single scalar value to the voxel, reflecting some form of average of its constituent fibres. Here, a new experimental framework that combines diffusion MRI and relaxometry is introduced. It provides, for the first time, the ability to assign to each unique fibre system within a voxel, a unique value of the longitudinal relaxation time, T 1, which is largely influenced by the myelin content. Methods: We demonstrate the method through simulations, in a crossing fibres phantom, in fixed brains and in vivo . Results: The method is capable of recovering unique values of T 1 for each fibre population. Conclusion: The ability to extract fibre‐specific relaxometry properties will provide enhanced specificity and, therefore, sensitivity to differences in white matter architecture, which will be invaluable in many neuroimaging studies. Further the enhanced specificity should ultimately lead to earlier diagnosis and access to treatment in a range of white matter diseases where axons are affected. Magn Reson Med 75:372–380, 2016. © 2015 The Authors. Magnetic Resonance in Medicine Published by Wiley Periodicals, Inc. on behalf of International Society of Medicine in Resonance.